Desempenho de filmes soprados multicamada de blendas de polipropileno e copolímeros de etileno - Elias, Marcelo Brasil (Universidade Federal de São Carlos, 2012)
Polypropylene (PP) and polyethylene (PE) are widely used in the flexible packaging market individually as mono or multilayer films. Blending PP and PE in coextruded films has shown limited commercial applications due to the poor adhesion. On this work we made three layer coextruded blown films with ascendant flow and air cooling. The thicknesses were kept constant at 50m, having the external layers made of metallocene ethylene-octene copolymers (m-PE) to provide sealability. The internal layer (structural) was produced with rich blends of polypropylene homopolymer and ethylene-octene copolymers made by metallocene (m-PE and POP) and by Ziegler-Natta (U-PE) catalytic systems. These films were characterized by their mechanical, thermal, optical and morphological properties. Based on the results it is proposed a morphological model of the core layer, in which the matrix phase of PP has a shish kebab crystalline structure, and the disperse phase and the external layers composed by fragmented lamellar crystallites blended with small spherulites. The epitaxial crystallization of the polyethylene copolymer on the shishes of the polypropylene allows good adhesion between the external and internal layers of the multilayered structure. The internal structure formed with the dispersed phase of m-PE and U-PE has shown similar mechanical behavior with better properties at the concentration of 30%.On the other hand, when the dispersed phase of the internal layer is POP elastomer, the Tg and Tm of the matrix PP decrease due the compatibility between the matrix and the dispersed phase, generating shish kebab structures with lower crystallinity. These morphological characteristics guarantee a balanced film regarding the thermomechanical properties, in order to achieve a high performance flexible packaging.
Performance of multilayer blown films of polypropylene and ethylene copolymers blends
Keywords: Polipropileno; Adesão; Cristalização; Polietileno; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA